2000
DOI: 10.1071/ar00017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seedling allelopathy in 453 wheat (Triticum aestivum) accessions against annual ryegrass (Lolium rigidum) by the equal-compartment-agar method

Abstract: Allelopathy has been receiving world-wide attention for its potential in integrated weed management. A newly developed screening bioassay, the ‘equal-compartment-agar method’ (ECAM), was used to evaluate seedling allelopathy against annual ryegrass in a collection of 453 wheat accessions originating from 50 countries. Significant differences in allelopathic potential were found in this worldwide collection, inhibiting root growth of ryegrass from 9.7% to 90.9%. Wheat seedling allelopathy also varied significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 13 publications
4
95
0
3
Order By: Relevance
“…The results of the current study are broadly in agreement with those of Wu et al (2000Wu et al ( , 2001, who also found a significant genetic variation of weed growth inhibitory activity in wheat and reported that wheat allelopathic activity is genetically controlled, and a multigenic model is involved in wheat allelopathy.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the current study are broadly in agreement with those of Wu et al (2000Wu et al ( , 2001, who also found a significant genetic variation of weed growth inhibitory activity in wheat and reported that wheat allelopathic activity is genetically controlled, and a multigenic model is involved in wheat allelopathy.…”
Section: Discussionsupporting
confidence: 81%
“…Although cv Tasman was strongly allelopathic, cv Sunco belonged to the intermediate allelopathic groups (Wu et al 2000a). To verify these initial results on the genetic control of wheat allelopathy, it is necessary to construct new mapping populations derived from two extreme allelopathic groups, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Recent research has generally shown that allelopathic activity is quantitatively inherited in rice and wheat (Dilday et al 1998;Wu et al 2000a). Wu et al (2000a) found that wheat-seedling allelopathy on L. rigidum was normally distributed in the collection of 453 wheat accessions, indicating that this weed-suppressing ability is a quantitative trait. The genetic control of allelopathic activity was further studied using near-isogenic wheat lines derived from Hartog (weakly allelopathic) Janz (strongly allelopathic).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Allelochemicals are generally secondary metabolites present in different concentrations in different plant parts (leaves, stem, barks, flowers, seeds etc.) which upon release into the rhizosphere tend to modify the resource consumption capacity by several mechanisms i.e., alteration of cell membrane permeability, changing enzymatic activity, triggering genetic defects and disturbing photosynthesis of the competitor plants (Gonzalez and Estevez-Braun, 1997;Wu et al, 2000;Barto et al, 2010;Majeed et al, 2012). Interactions among plants for resources through allelopathy lead to physiological and biochemical modifications which may result in the establishment of a successful plant community by eliminating or restricting the susceptible species, although many plants exhibit positive allelopathic effects on the surrounding plants (Elijarrat and Barcelo, 2001;Maharjan et al, 2007;Hussain et al, 2010).…”
Section: Introductionmentioning
confidence: 99%